The Relative Efficiency of Public and Private Firms in a Competitive Environment: The Case of Canadian Railroads - Caves, Douglas W.; Christensen, Laurits R. (Journal of Political Economy, 1980)
The efficiency of public and private firms is usually compared in industries which have heavy regulation and limited competition. In this paper we present a case study in which the effects of property rights can be isolated from the effects of regulation on noncompetitive markets. We compare the postwar productivity performance of the Canadian National and Canadian Pacific Railroads. Contrary to the predictions of the property rights literature, we find no evidence of inferior performance by the government-owned railroad. We conclude that any tendency toward inefficiency resulting from public ownership has been overcome by the benefits of competition.